Diogenes Syndrome: Case Report - Jorge Luiz de Carvalho Mello; Renata Santos Alves; Lívia Caramaschi Florêncio; Marcela de Medeiros Fregonesi; Thaís Cristina Carvalho; Monize Spazzapan Martins (Brazilian Society of Geriatrics and Gerontology, 2024)
Hoarding disorder (HD) can be defined as a persistent difficulty with the disposal of items due to the suffering associated with the elimination or the perceived need to keep them, regardless of their real value. In the elderly, HD is related to another condition called domestic squalor. Accumulation is associated with a specific form of pathological self-neglect in this population referred as Diogenes syndrome (DS), which consists of extremely poor hygiene and inability to maintain adequate self-care routines, along with compulsive collectionism. The authors describe a case of HD, referred here as DS, in an elderly patient, emphasizing the importance of early detection, differential diagnosis, investigation, multidisciplinary intervention, and pharmacotherapy.